Endobronchial valve block in the treatment of patients with destructive pulmonary tuberculosis and low adherence to therapy with anti-tuberculosis drugs and refusing to stay in hospital - P. A. Fadeev; D. V. Krasnov; S. V. Sklyuev; N. G. Grischenko; V. A. Krasnov (Туберкулез и болезни лёгких)
The objective of the study: to analyze the efficacy of endobronchial valve block (EBV) during out-patient treatment of patients with destructive pulmonary tuberculosis who refused in-patient treatment and therapy with anti-tuberculosis drugs.Subjects and methods. Treatment outcomes of 129 patients were randomly studied, the patients suffered from destructive pulmonary tuberculosis and demonstrated low adherence to therapy with anti-tuberculosis drugs and staying in hospital. EBV was used in one group (66 patients), and it was not used in patients from another group (63 patients). Results. The use of EBV in patients with poor adherence to inpatient treatment and chemotherapy allowed achieving sputum conversion in 36 (58.1%) patients and healing of cavities in 43 (65.2%). Among the patients in whom no EBV was used, sputum conversion was achieved in 12 (20.7%) patients (p = 0.001, χ2) and cavities were healed in 14 (22.2%) patients (p = 0.001, χ2). Efficacy and safety of EBV was demonstrated when used on the out-patient basis in the above category of patients.